Policing same-sex relations in eighteenth-century Paris: archival voices from 1785 - Merrick, Jeffrey (The Pennsylvania State University Press, 2024)
"An English translation of recorded depositions by men arrested for sodomy or pederasty in eighteenth-century Paris, exploring complex questions about sources, patterns, and meanings in the history of sexuality"--